Expression of Genes Involved in ABA and Auxin Metabolism and LEA Gene during Embryogenesis in Hemp - Král, Daniel; Šenkyřík, Josef Baltazar; Ondřej, Vladan (Plants (Basel, Switzerland), 2022)
The level of phytohormones such as abscisic acid (ABA) and auxins (Aux) changes dynamically during embryogenesis. Knowledge of the transcriptional activity of the genes of their metabolic pathways is essential for a deeper understanding of embryogenesis itself; however, it could also help breeding programs of important plants, such as Cannabis sativa, attractive for the pharmaceutical, textile, cosmetic, and food industries. This work aimed to find out how genes of metabolic pathways of Aux (IAA-1, IAA-2, X15-1, X15-2) and ABA (PP2C-1) alongside one member of the LEA gene family (CanLea34) are expressed in embryos depending on the developmental stage and the embryo cultivation in vitro. Walking stick (WS) and mature (M) cultivated and uncultivated embryos of C. sativa cultivars 'KC Dora' and 'USO 31' were analyzed. The RT-qPCR results indicated that for the development of immature (VH) embryos, the genes (IAA-1, IAA-2) are likely to be fundamental. Only an increased expression of the CanLea34 gene was characteristic of the fully maturated (M) embryos. In addition, this feature was significantly increased by cultivation. In conclusion, the cultivation led to the upsurge of expression of all studied genes.
Keywords: RT-qPCR; embryogenesis; LEA gene; auxin; abscisic acid; gene expression; Cannabis sativa; embryo cultures